2022
DOI: 10.3390/insects14010005
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effective PCR-Based Identification of Tunga penetrans (Siphonaptera) Larvae Extracted from Soil Samples Containing PCR Inhibitor-Rich Material

Abstract: Tungiasis is a neglected tropical disease caused by skin-penetrating female Tunga penetrans fleas. Although tungiasis causes severe health problems, its ecology is poorly understood and morphological descriptions of the larvae are unavailable. To identify T. penetrans immature stages and sites where they develop, diagnostic PCRs are required. However, flea larvae feed on soil organic matter rich in PCR inhibitors. Here, three DNA preparation methods, including a soil DNA kit that removes inhibitors, a simple a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Samples were collected from sleeping areas of tungiasis-infected members in the context of field sampling activities of larger risk factor surveys prepared for publication elsewhere. The soil samples were exposed to heat using a Berlese Tullgren funnel (Amugune et al 2022). Tunga larvae were identified morphologically under a microscope (Hicks 1930, Nagy et al 2007) and their identity was confirmed through PCR-based methods (Amugune et al 2022).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples were collected from sleeping areas of tungiasis-infected members in the context of field sampling activities of larger risk factor surveys prepared for publication elsewhere. The soil samples were exposed to heat using a Berlese Tullgren funnel (Amugune et al 2022). Tunga larvae were identified morphologically under a microscope (Hicks 1930, Nagy et al 2007) and their identity was confirmed through PCR-based methods (Amugune et al 2022).…”
Section: Methodsmentioning
confidence: 99%
“…The soil samples were exposed to heat using a Berlese Tullgren funnel (Amugune et al 2022). Tunga larvae were identified morphologically under a microscope (Hicks 1930, Nagy et al 2007) and their identity was confirmed through PCR-based methods (Amugune et al 2022). Larvae were gently transferred to a larval medium, a mixture of a pinch of fish food (Tropical Flake Fish Food, Supa Aquatic Supplies Ltd., Sheffield, UK) and soil, and reared till pupation at ambient conditions at 24.2–29.0°C, natural light and at a relative humidity of 60%–99%.…”
Section: Methodsmentioning
confidence: 99%